The role of a starch-based diet in solving existential challenges for the 21st century - McDougall, John (Frontiers in Nutrition, 2023)
Diet plays a fundamental role in our major chronic diseases, in climate change, and in our resistance to infectious diseases. The eating patterns that best support the health of people and our planet are based on traditional starchy staples. Historically, a wide variety of starches have provided the bulk of the food for most of the people who have walked our Earth. For example, rice has been food for Asians, corn for Central Americans, potatoes for people of the Andes, and for the Middle East, "the bread basket of the world," food has meant wheat and barley. Focusing on our ethnicities can expose altruistic natures, and before it is too late, allow us to make the change from destructive animal-food baseddiets to plant-food based-diets; ones that are health-supporting for people and our planet.